The Impact of Broadband on U.S. Agriculture: An Evaluation of the USDA Broadband Loan Program. (19th March 2017) - Kandilov, Amy M.G.; Kandilov, Ivan T.; Liu, Xiangping; Renkow, Mitch
Abstract: We evaluate the impact that the USDA's low‐cost broadband loan programs have on the U.S. agricultural sector. The broadband loan programs increase access to high‐speed Internet in recipient communities, which can raise farm sales by increasing both farm output and prices received by producers. Further, high‐speed Internet may drive down costs by providing information on cheaper inputs and better management practices, leading to an overall improvement in farm profits. Using U.S. county‐level data on farm sales and expenditures in 2000 and 2007, we employ an inverse probability weighting technique to control for endogenous selection in an econometric model that also accounts for spatial dependence. We find that the two USDA broadband loan programs have had positive causal impacts on farm sales, expenditures, and profits in a subset of rural counties—those adjacent to metropolitan counties—but not in other types of counties.